Price-concentration analysis in merger cases with differentiated products - Walter Beckert; Nicola Mazzarotto (Economics: The Open-Access, Open-Assessment E-Journal, 2010)
This paper considers the empirical assessment of the relationship between prices and number of firms in local markets in geographic or, more generally, characteristic space and its use as evidence in merger cases. It outlines a structural, semi-nonparametric econometric model of competition in such markets, examines its testable implications in terms of price-concentration relationships, and demonstrates that the model is non-parametrically identified. This general approach to price-concentration analysis in differentiated product markets is illustrated in a small-scale application to cinemas in the UK. The application highlights the main decision points faced by an authority when assessing the weight that can be attached to this type of analysis as evidence.
Keywords: L11; C31; 330; Differentiated products; local competition; non-parametric identification; Räumliche Preistheorie; Produktdifferenzierung; Fusionskontrolle; Wirtschaftskonzentration; Nichtparametrisches Verfahren; Schätzung; Kinowirtschaft; Großbritannien